A novel predator-prey strategy for optimization problems: preliminary study - Cavaleiro Costa, Sérgio (2021)
Several evolutionary algorithms are described in the literature, but few try to mimic the predator-prey behavior. A novel Predator-Prey Algorithm is presented here, where several species may prey each other and reproduce, pushing the overall population to the best solutions of the cost function. This algorithm not only proved to be capable of finding solutions, but a niching behavior emerged from the algorithm itself, which is very desirable in multiobjective problems.